2009
DOI: 10.3168/jds.2008-1613
|View full text |Cite
|
Sign up to set email alerts
|

Grazing cows are more efficient than zero-grazed and grass silage-fed cows in milk rumenic acid production

Abstract: Six rumen-cannulated Holstein cows in early lactation were assigned to 3 treatments: grazing (G), zero-grazing (ZG), and grass silage (GS) harvested from the same perennial rye grass sward in a 3 x 3 Latin square design with three 21-d periods. The objectives of this study were to investigate the underlying mechanisms for the reported elevation in milk rumenic acid (RA) concentration associated with G compared with ZG and GS, and to identify the important variables contributing to the milk RA response. Grazing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
59
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 44 publications
(48 reference statements)
7
59
2
2
Order By: Relevance
“…Los estudios revisados indican que aproximadamente un 75 % de la variabilidad en el contenido de ALC en la leche se puede explicar por el consumo total de sus precursores (ácido linoleico y linolénico) presentes en el alimento (Mohammed et al 2009). …”
Section: Discussionunclassified
“…Los estudios revisados indican que aproximadamente un 75 % de la variabilidad en el contenido de ALC en la leche se puede explicar por el consumo total de sus precursores (ácido linoleico y linolénico) presentes en el alimento (Mohammed et al 2009). …”
Section: Discussionunclassified
“…In most studies, rumen pH measurements were generally taken either once (Tajima et al, 2001), twice (Abughazaleh et al, 2003;Mohammed et al, 2009), four times (Klieve et al, 2003) or six times a day (Kalscheur et al, 1997;Kim et al, 2008). It proved difficult to relate the selected pH measurements to changes in rumen bacterial population (Klieve et al, 2003;Kim et al, 2008), or to specific fatty acid (FA) metabolite (ruminal t10-18:1; Mohammed et al, 2009). Therefore, in this study we utilized a continuous rumen pH monitoring system (Penner et al, 2006) to determine rumen pH changes more accurately and relate them to the PUFA intermediates in the rumen.…”
Section: Introductionmentioning
confidence: 99%
“…Rumen samples for FA analysis consisted of both fluid and solids and were collected at the same time as described for VFA and NH 3 analyses and stored at 2208C. For FA analysis, the samples were freeze-dried and milled and 0.5 g of the sample pooled by cow each period was utilized for FA analysis following the protocol described by Mohammed et al (2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent studies have shown that endogenous synthesis contributes a large proportion of total CLA in milk, with estimates including 64 (Griinari et al, 2000), 78 (Corl et al, 2001), 94 (Kay et al, 2004) and 93% to 97% (Piperova et al, 2002;Mohammed et al, 2009), depending on diet composition, oil supplementation and grazing. However, reasons for increased synthesis with regimens that are known to be effective in increasing milk CLA remain unclear.…”
Section: Introductionmentioning
confidence: 99%